Combination chemotherapy with sintilimab for treatment of a male patient with primary pulmonary choriocarcinoma: a case report and literature review - Liang, Xiaojing; Xu, Guoqing; Zhang, Jisong; Xu, Li; Dong, Liangliang; Wang, Xiaoyue; Han, Weidong; Chen, Enguo (Frontiers in Immunology, 2025)
Primary pulmonary choriocarcinoma (PPC) is an extremely rare malignant cancer in men with no clinical guidelines for the treatment. Cytotoxic chemotherapy has a limited effect on the prognosis of PPC. Recently, immune checkpoint inhibitors (ICIs) have shown promising treatment effectiveness. A literature review revealed that a combination of chemotherapy and ICIs could prolong the survival time of PPC patients. Herein, we report a 67-year-old man with a cough, expectoration, and blood in the sputum, presenting with a mass in the lower lobe of the right lung. The hematoxylin and eosin staining and immunohistochemical profile of the primary lesion showed features of choriocarcinoma, accompanied by elevations in serum human chorionic gonadotropin (HCG) levels. Programmed death-ligand 1 (PD-L1) expression was positive (70%) in the 22C3 assay. He received a combination of cisplatin, etoposide, paclitaxel, and sintilimab. Four months after the treatment began, chest computed tomography (CT) showed significant mass reduction. Therefore, ICIs may be a promising therapy option for patients with PPC.